(untitled) (Journal of Informatics Education and Research, 2024)
The process of turning around an individual’s sense of self-sufficiency shall be called as empowerment. The proposed study has been carried out for civil engineers’ population in India and the sample has been picked from Telangana state in India. Real estate is booming because of employment opportunities and infrastructure is developed to meet the needs of the public. The study intended to understand the civil engineer’s psychological empowerment ramification over their organization commitment. The study constructed based on secondary data as well as primary data. The primary data has been collected by administering the questionnaire through snow ball technique. The primary data has been analyzed using the SPSS. The primary data is found to be good and acceptable as the value of Cronbach’s alpha is being more than 0.70. The calculated t-value is more than tcritical value as well as F value is more than Fcritical. Considering the results, it is concluded that the statements of psychological empowerment meaning/ful, competencies very strongly determine the organization commitment; self-determination, impact strongly determines the organization commitment whereas the psychological empowerment variable strongly determines the organization commitment. The regression models are generated and incorporated in the study. The study results are in line with Bhatnagar 2007; Joo & Shim 2010; Chen and Chen 2008; Hashmi and Naqvi 2012; Huang, Shi, Zhang, & Cheung, 2006 conclusion. The findings of Laschinger, Finegan, Shamian, and Wilk (2001) provide some corroboration of Chan’s (2003) findings about the connection between employee empowerment and ongoing commitment. They discovered that it was feeble. The study reveals that psychological empowerment is predicted by an emotive, normative, and continuous participation in our Indian sample.